(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
A chest drain is a medical tube that is inserted between the ribs in the space between the lung and internal chest wall. Air or fluid can leak into the space around the lung after infection or injury which is drained by the tube, allowing the lung to re-expand. Inserting a chest drain can be lifesaving, and it is estimated that, world-wide, millions of chest drains are inserted annually. This paper presents the design and 3D printing of the initial product development of an advanced functional prototype of a breakaway chest drain valve. This breakaway chest drain valve seeks to address the accidental removal from the patient, and to allow intentional removal and reconnection stopping air and fluid re-entering the chest. As such, this research investigates how the novel design for a breakaway valve as part of a chest drain kit could reduce the chances of drains becoming dislodged from a patient, and allow for intentional disconnection when repositioning a patient, potentially reducing patient trauma, and saving time and costs to healthcare providers. Acknowledgments This research is funded by the National Institute for Health and Care Research - i4i Product Development Awards (PDA) - Breakaway Chest Drain Valve (Reference: NIHR204562). The porcine testing conducted was prior to acquiring NIHR i4i funding and was neither funded of associated with the NIHR. The authors would like to acknowledge Mr Joseph Meeks for his work with early prototyping, product development and parameter testing. Furthermore, the authors would like to acknowledge the technical support provided by technicians and technical specialists based in the School of Architecture Design & Built Environment and the Department of Engineering at Nottingham Trent University. Author’s statement Conflict of interest: Authors state no conflict of interest. Informed consent: Informed consent has been obtained from all individuals included in this study.